1996
DOI: 10.4319/lo.1996.41.8.1758
|View full text |Cite
|
Sign up to set email alerts
|

The fate of marine autotrophic production

Abstract: The fate of photosynthetic carbon in marine ecosystems dominated by different types of primary producers was examined by compiling published reports on herbivory, autotrophic respiration, decomposition, carbon storage, and export rates as fractions of net primary production (NPP) in ecosystems dominated by different types of autotrophs (i.e. oceanic and coastal phytoplankton, microphytobe.lthos, coral reef algae, macroalgae, seagrasses, marsh plants, and mangroves). A large fraction (>40%) of ,.he NPP of marin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
572
3
15

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 827 publications
(611 citation statements)
references
References 43 publications
21
572
3
15
Order By: Relevance
“…This variability was correlated with climate (river flow and temperature) and long-term tidal exposure cycles. Recent evidence has confirmed that seagrass meadows are one of the most productive shallow water ecosystems (Margalef 1986, Stevenson 1988, Duarte & Cebrian 1996, Duarte & Chiscano 1999, Rasheed et al 2008. These findings present concern given the expected future climate scenarios of increased temperatures and more variable rainfall.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This variability was correlated with climate (river flow and temperature) and long-term tidal exposure cycles. Recent evidence has confirmed that seagrass meadows are one of the most productive shallow water ecosystems (Margalef 1986, Stevenson 1988, Duarte & Cebrian 1996, Duarte & Chiscano 1999, Rasheed et al 2008. These findings present concern given the expected future climate scenarios of increased temperatures and more variable rainfall.…”
Section: Discussionmentioning
confidence: 84%
“…While these meadows constitute only a small fraction of the global marine primary production (1.13%), they play an important role as a carbon sink (Duarte & Cebrian 1996, Kennedy & Björk 2009). Seagrass meadows also provide important ecosystem services, such as nutrient cycling (Costanza et al 1997), providing refuge for highly productive fauna (Unsworth et al 2008 and supporting subsistence and commercial fisheries (Watson et al 1993, Unsworth & Cullen 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The inputs of total organic carbon (TOC) from the coastal ocean to the dark open ocean have been estimated at 0.17 Pmol C a −1 (e.g. Liu et al 2000), representing a significant fraction of the global TOC export from the coastal to the open ocean, which have been estimated to range from 0.23 Pmol C a −1 (Gattuso et al 1998) to 0.5 Pmol C a −1 (Duarte and Cebrián 1996;Duarte et al 1999).…”
Section: Coastal Inputs To the Dark Oceanmentioning
confidence: 99%
“…Yearly at the end of summer, the seagrass losses a major part of its leaf biomass after senescence. The fate of these P. oceanica dead leaves, also called leaf litter, varies (Pergent et al, 1997): a part of the leaf litter decays slowly or is buried within the meadow, while another part is exported to other adjacent habitats where it may represent a considerable organic material input (Cebrian et al, 1997;Duarte and Cebrian, 1996;Romero et al, 1994). Such exported leaf litter mixes with drift epilithic macroalgae, uprooted living seagrass shoots with rhizomes, other seagrass litter, seeds, dead macrofauna and fine sediment to form detritus.…”
Section: Introductionmentioning
confidence: 99%